Photocatalytic degradation of a mixture of eight antibiotics using Cu-modified TiO2 photocatalysts: Kinetics, mineralization, antimicrobial activity elimination and disinfection. Issue 4 (August 2021) - Evgenidou, Eleni; Chatzisalata, Zoi; Tsevis, Athanasios; Bourikas, Kyriakos; Torounidou, Pavlina; Sergelidis, Daniel; Koltsakidou, Anastasia; Lambropoulou, Dimitra A.
Abstract: In the present study the photocatalytic degradation of a mixture of eight antibiotics using Cu-modified TiO2 photocatalysts has been explored. The catalysts have been synthesized following the Equilibrium Deposition Filtration (EDF) method and were characterized by different techniques such as X-ray Powder Diffraction (XRD), Transition electron microscopy (TEM), UV–vis Diffuse Reflectance Spectroscopy (DRS) etc. Their photocatalytic activity was investigated towards a mixture of antibiotics including isoniazid, metronidazole, sulfadiazine, sulfamethoxazole, trimethoprim, norfloxacin, moxifloxacin and lincomycin. Complete degradation was achieved within 30 min while various parameters were explored as the amount of modifier, the concentration of the catalyst, the effect of matrix and the participation of the reactive species. The most efficient catalyst (with 0.8 wt% Cu loading) was further tested against mineralization achieving a 75% reduction of total organic carbon within 6 h while almost complete detoxification on daphnia was achieved within the same time period. Moreover, photocatalytic treatment led also to complete elimination of the residual antimicrobial activity. Finally, the 0.8 wt% Cu-modified catalyst proved to be efficient on disinfection of a wastewater effluent against E. coli . Graphical Abstract: ga1 Highlights: Cu-doped catalysts with 0.1–4.9 wt% Cu loading were synthesized and characterized. The catalysts were able to degrade a mixture of eight antibiotics. Various parameters like the amount of dopant or the effect of matrix were explored. Significant reduction of toxicity and residual antimicrobial activity was achieved. Disinfection against E. coli was accomplished within 90 min of treatment.